6(9y+2)-9= -3
-3(2y - 5)=3(1 - 3y) +14
4(x - 1)- (5x - 7) = 2(5x - 1) - 17
2(4x - 2) - (5x - 8) = 9 - (3x + 2 )
Please help me on how to solve these!! thank you so much.. i ask this in another form but i was still confused by some answers that were given by users..

1.
6(9y+2)-9= -3
54y + 12 -9 = -3
54y + 3 = -3
subtract 3 from each side
54y = -6
divide each side by 54
y = -6/54 = -1/9
2.
-3(2y - 5)=3(1 - 3y) +14
-6y + 15 = 3 - 9y +14
-6y+15+9y = 3 -9y +14+9y
3y +15 = 17
subtract 15 from each side
3y = 2
divide each side by 3
y = 2/3
3.
4(x - 1)- (5x - 7) = 2(5x - 1) - 17
4x - 4 -5x + 7 = 10x - 2 -17
-x + 3 = 10x - 19
3 = 11x - 19
3 + 19 = 11x
22 = 11x
divide each side by 11
x = 22/11=2

4).

2(4x - 2) - (5x - 8) = 9 - (3x + 2 )

Apply distributive property of subtraction : a(b - c) = ab - ac.

8x - 4 - 1(5x - 8) = 9 - 1(3x + 2)

Apply distributive property of subtraction : a(b - c) = ab - ac.

8x - 4 - 5x + 8 = 9 - 1(3x + 2)

Apply distributive property of addition : a(b + c) = ab + ac.

8x - 4 - 5x + 8 = 9 - 3x - 2

Group like terms.

(8x - 5x) + 4 = 7 - 3x

3x + 4 = 7 - 3x

3x + 3x + 4 = 7 - 3x + 3x

6x + 4 = 7

Subtract 4 from each side.

6x + 4 - 4 = 7 - 4

6x = 3

Divide each side by 6.

6x/6 = 3/6

x = 1/2.